Wybrane czynniki kształtujące wzrost i utrzymanie konkurencyjności na przykładzie przedsiębiorstw branży drobiarskiej - Banaś, Katarzyna (Selected Factors Running Increase and Maintenance of Competitive on Example of Firms of Poultry Trade, 2006)
In production of poultry livestock costs of fodder determine greatest participation in productive outlays. The aim of undertaken investigations was analysis of productive and economic results in farms basing on own fodder and from purchase, differing with scale of production. It was stated that most profitable production running subjects basing on own fodder, producing in great scale.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 51-56